Psychoanalysis of the mobile money ecosystem in the digital age: generational cohort and technology generation theoretical approach. Issue 8 (17th November 2022) - Okello Candiya Bongomin, George; Yourougou, Pierre; Yosa, Francis; Manzi, Alain Amani; Ntayi, Joseph Mpeera
ABSTRACT: The primary purpose of this study is to establish the moderating role of generational differences in the relationship between mobile money adoption and use and financial inclusion in developing countries. Three key findings emerged: first, there is a moderating role of generational differences on mobile money adoption and use; second, both mobile money adoption and use and generational differences have significant and positive effects on financial inclusion; third, the inclusion of generational differences, as a moderator, results in 6.7 per cent increase in financial inclusion in developing countries.